Carbon fiber material, preparation method thereof and lithium ion battery
By using a low eutectic solvent and fiber biomass carbon for high-temperature graphitization treatment, graphitized carbon fiber materials with porous network structure and micropores were prepared, which solved the problems of high energy consumption and insufficient performance of carbon fiber graphitization in the prior art. , achieving efficient lithium storage performance and conductivity.
Patent Information
- Application Number
- CN202210683402.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-16
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-06-16
AI Technical Summary
The prior art has problems in the process of graphitization of carbon fibers with high energy consumption and difficulty in obtaining high-performance graphitized carbon fibers.
Eutectic solvents (such as halocholine and haloferrous iron salts) are mixed with fiber-based biomass carbon, and then graphitized after high temperature to form graphitized carbon fiber materials with porous network structure and micropores.
It improves the specific surface area and lithium storage performance of carbon fiber, enhances the conductivity and rate performance, reduces the graphitization temperature, and is suitable for industrial production.
Smart Images

Figure CN115058794B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of new energy technology, and relates to a carbon fiber material, a preparation method thereof and a lithium ion battery. Background Art
[0002] Carbon fiber has the advantages of light weight, high strength, good heat resistance and corrosion resistance, and is widely used in sports equipment, aerospace, rail transportation, automobiles and other fields. Graphitization of carbon fiber can make its structure tend to the ideal graphite structure, greatly improve the tensile modulus, and has good heat shock resistance, small thermal expansion coefficient, can withstand 3500℃ in the absence of oxygen, excellent flame retardancy and electrical conductivity, and corrosion resistance. Therefore, the study of graphitization of carbon fiber is of great significance to its promotion and application.
[0003] The core of carbon fiber graphitization technology is to perform ultra-high temperature heat treatment on carbon fiber. The graphitization temperature of general carbon materials is generally around 2500℃, and the energy consumption is relatively high. For example, CN110409018A discloses a method for preparing dry-jet wet-spinning high-strength and wear-resistant polyacrylonitrile-based carbon fiber, and the preparation method comprises: step 1, graphitization: the carbonized fiber obtained by pre-oxidation and carbonization of dry-jet wet-spinning polyacrylonitrile precursor is subjected to graphitization heat stretching treatment at 2300-2500℃, the graphitization time is 60-120s, and the stretching ratio is 1.01-1.04; step 2, surface treatment, using anodizing electrochemical treatment, the graphitized carbon fiber obtained in step 1 is surface treated, the electricity is 50-100C / g, and finally sizing, drying, and the sizing agent content is 1.0-1.5%, to obtain high-strength, high-modulus and wear-resistant polyacrylonitrile-based carbon fiber. CN111962287A discloses a process for preparing high-performance, low-cost graphitized carbon fibers using Joule heat technology, wherein high-performance, low-cost graphitized carbon fibers are prepared by introducing Joule heat heating method, that is, the elastic modulus of the obtained graphitized carbon fibers is higher than 350MPa. At the same time, since the conductive and resistive properties of the carbon fibers are utilized to directly pass electricity on the carbon fibers themselves, the carbon fibers can be heated by this method to a temperature of up to 2800°C.
[0004] As can be seen from the above, the existing technology generally fiberizes carbon fibers by high-temperature heating, but there is a problem of high energy consumption, and it is a major research problem to improve its structure to obtain high-performance graphitized carbon fibers. Therefore, it is of great significance to study a high-performance graphitized carbon fiber and its preparation and modification methods. Summary of the invention
[0005] The purpose of the present invention is to provide a carbon fiber material, a preparation method thereof and a lithium ion battery.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a carbon fiber material, wherein the carbon fiber material comprises graphitized carbon fibers, wherein the graphitized carbon fibers are overlapped with each other to form a porous network structure, and wherein the graphitized carbon fibers have micropores on their surfaces.
[0008] The carbon fiber material of the present invention has a porous network structure, and there are many nanostructured gaps formed by interlacing carbon fibers between the carbon fibers, which is very beneficial to the diffusion of electrolyte and the deintercalation of lithium ions, and is beneficial to improving the specific surface area and lithium storage performance of the material. At the same time, compared with ordinary carbon fibers, graphitized carbon fibers have better conductivity. At the same time, the micropores on the surface of graphitized carbon fibers are beneficial to the storage of lithium adsorbed ions on the surface and edges of the carbon fibers, thereby increasing the capacity.
[0009] The carbon fiber material of the present invention is used as a negative electrode active material and / or as a conductive agent to make an electrode and is applied to a lithium ion battery, and has the advantages of high capacity, good conductivity and excellent rate performance.
[0010] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0011] Preferably, the micropores are obtained by etching the fibrous biomass carbon using flue gas of a low eutectic solvent, wherein the low eutectic solvent comprises halogenated choline and halogenated iron salt.
[0012] Preferably, in the XRD spectrum of the carbon fiber material, the ratio of the main peak intensity of the (002) crystal plane to the total intensity of the miscellaneous peaks is 2-5:1. The ratio of the main peak to the miscellaneous peak reflects the degree of graphitization in the carbon fiber material. The present invention can adjust the degree of graphitization in the carbon fiber material by adjusting the ratio of the main peak to the miscellaneous peak, thereby enabling the lithium battery using the carbon fiber material to have a higher first efficiency, good cycle performance and rate performance. For example, the ratio of the main peak to the miscellaneous peak can be adjusted by adjusting the sintering temperature, thereby adjusting the degree of graphitization in the carbon fiber material.
[0013] In a second aspect, the present invention provides a method for preparing the carbon fiber material as described in the first aspect, the method comprising the following steps:
[0014] (1) heating and mixing a choline halide and a ferric halide to form a deep eutectic solvent;
[0015] (2) mixing the fibrous biomass carbon with the low eutectic solvent to obtain a precursor;
[0016] (3) subjecting the precursor to high-temperature graphitization treatment to obtain a carbon fiber material;
[0017] The temperature of the high temperature graphitization treatment is 1400-1800°C.
[0018] Pores in carbon fibers can increase the lithium storage capacity in the carbon layer and on the surface of the carbon layer. Generally, pores are formed on the carbon fibers by adding pore-forming agents (such as polyvinyl alcohol (PVA), polyvinyl butyral (PVB), etc.). However, additional pore-forming agents need to be added in advance and mixed and stirred, which increases the cost and reaction steps.
[0019] The method of the present invention first heats and mixes halogenated choline and halogenated iron salt to form a low eutectic solvent. The cellulose in the fibrous biomass carbon is insoluble in water, but can swell in the low eutectic solvent to form a homogeneous mixture, which can play a role in exfoliating the cellulose. During the high-temperature graphitization process, the flue gas carbonized by choline is alkaline, thereby generating a corrosion pore-forming effect, thereby increasing the specific surface area and lithium storage performance of the biomass carbon.
[0020] Among them, due to the addition of iron elements in the low eutectic solvent, an iron complex will be formed in the low eutectic solvent, which will adsorb the reactants and catalyze and dissolve carbon during the high-temperature graphitization treatment. When the carbon solubility reaches saturation or supersaturation, part of the melted carbon tends to a low-energy graphite crystal form and precipitates, thereby reducing the graphitization temperature and obtaining a carbon fiber material.
[0021] Different from the conventional carbon fiber preparation method which uses petrochemical raw materials and grain raw materials as carbon sources, the present invention uses fiber biomass carbon, a non-grain biomass, as the carbon source. The reaction process is environmentally friendly, controllable, and highly industrialized. In addition, the carbon fiber conductive material obtained by the method of the present invention has excellent performance.
[0022] In the method of the present invention, since the fiber biomass carbon is directly carbonized with the low eutectic solvent, the phenomenon of uneven mixing of reactants in the precursor during the usual carbonization process is avoided, thereby improving the carbonization efficiency and uniformity, and is suitable for industrial production.
[0023] Preferably, the choline halide in step (1) comprises at least one of choline chloride, choline bromide or their derivatives.
[0024] Preferably, the halogenated iron salt in step (1) includes any one or more of ferric chloride, ferrous chloride, ferrous bromide or their derivatives.
[0025] Preferably, in step (1), the molar ratio of the choline halide to the halogenated iron salt is (1-3):(2-8), wherein the selection range of the choline halide 1-3 can be, for example, 1, 1.5, 1.6, 1.8, 2, 2.4, 2.5, 2.8 or 3, and the selection range of the halogenated iron salt 2-8 can be, for example, 2, 2.5, 3, 3.5, 4, 4.2, 4.5, 5, 5.5, 6, 6.5, 7 or 8, etc.
[0026] Preferably, the temperature of the heating and mixing in step (1) is 40-80°C, for example 43°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, etc.; the time is 2-8h, for example 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 6h, 6.5h, 7h or 8h, etc.
[0027] Preferably, the heating and mixing process in step (1) is accompanied by stirring.
[0028] Preferably, the fiber biomass carbon in step (2) is non-food biomass, preferably at least one of bamboo fiber, wood cellulose or their derivatives.
[0029] Preferably, in step (2), the mass ratio of the fibrous biomass carbon to the low eutectic solvent is (1-3):(2-8), wherein the selection range of the fibrous biomass carbon 1-3 can be, for example, 1, 1.5, 1.8, 2, 2.5 or 3, and the selection range of the low eutectic solvent 2-8 can be, for example, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5 or 8, etc.
[0030] Preferably, the mixing temperature in step (2) is 40-80°C, for example 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, etc.; the mixing time is 2-8h, for example 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 7h or 8h, etc.
[0031] Preferably, the mixing process in step (2) is accompanied by stirring.
[0032] Preferably, after the mixing in step (2), ultrasonic oscillation and standing are sequentially performed.
[0033] Preferably, the ultrasonic oscillation is performed at room temperature.
[0034] Preferably, the ultrasonic oscillation time is 20-60 min, for example, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, etc.
[0035] Preferably, the standing time is 1-2 h, such as 1 h, 1.3 h, 1.5 h, 1.6 h, 1.8 h or 2 h.
[0036] Preferably, before the high-temperature graphitization treatment in step (3), the precursor is pre-oxidized.
[0037] Preferably, the temperature of the pre-oxidation treatment is 200-300°C, such as 200°C, 220°C, 240°C, 260°C, 280°C or 300°C, etc.; the holding time is 1-2h, such as 1.2h, 1.4h, 1.6h or 2h, etc.
[0038] Preferably, the heating rate of the pre-oxidation treatment is 2-5°C / min, such as 2°C / min, 3°C / min, 4°C / min or 5°C / min.
[0039] Preferably, the atmosphere of the pre-oxidation treatment is an oxygen-containing atmosphere, preferably an air atmosphere.
[0040] Through pre-oxidation treatment, the organic matter in the mixture can be slowly decomposed and evaporated to form pores, which is conducive to obtaining high-performance carbon fiber materials.
[0041] The temperature of the high temperature graphitization treatment in step (3) is 1400-1800°C, for example, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C, 1650°C, 1700°C, 1750°C or 1800°C; the insulation time is 6-16h, for example, 6h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h or 16h.
[0042] Preferably, the heating rate of the high temperature graphitization treatment in step (3) is 2-5°C / min, for example, 2°C / min, 3°C / min, 4°C / min or 5°C / min.
[0043] Preferably, the atmosphere of the high temperature graphitization treatment in step (3) is an inert atmosphere, and the gas in the inert atmosphere includes at least one of nitrogen, helium and argon.
[0044] Preferably, after the high temperature graphitization treatment in step (3), the steps of pickling, washing, separation, ball milling and screening are sequentially performed. The present invention does not specifically limit the separation method, for example, it can be standing, filtering, etc. The sequential washing and separation is regarded as a cycle, and the number of cycles can be one or more.
[0045] Preferably, the solvent used for pickling is a pickling solvent, and the pickling solvent includes at least one of hydrochloric acid, sulfuric acid and acetic acid.
[0046] Preferably, the solvent used for the cleaning is anhydrous ethanol.
[0047] Preferably, the ball mill has a rotation speed of 500-1000 r / min, such as 500 r / min, 600 r / min, 750 r / min, 800 r / min, 900 r / min or 1000 r / min, etc.; and a ball milling time of 4-6 h, such as 4 h, 4.5 h, 5 h, 5.5 h or 6 h, etc.
[0048] Preferably, the mesh number of the sieving is 180-400 mesh, such as 200 mesh, 300 mesh or 400 mesh, and the sieve is taken after sieving.
[0049] As a further preferred technical solution of the method for preparing the carbon fiber material of the present invention, the method comprises the following steps:
[0050] 1) weighing choline halide and ferric halide in a molar ratio of 1-3:2-8, stirring at 40-80° C. in a constant temperature magnetic stirrer for 2-8 h to obtain a deep eutectic solvent;
[0051] 2) weighing a non-food biomass carbon source and a deep eutectic solvent in a mass ratio of 1-3:2-8, stirring at 40-80° C. in a constant temperature magnetic stirrer for 2-8 hours to obtain a mixture;
[0052] 3) The mixture obtained in step 2) is subjected to ultrasonic oscillation at room temperature for 20-60 minutes using an ultrasonic machine, and then allowed to stand for 1-2 hours to obtain a precursor;
[0053] 4) heating the precursor obtained in step 3) to 200-300° C. at a heating rate of 2-5° C. / min in an air atmosphere, and keeping the temperature for 1-2 hours; then heating the precursor to 1400-1800° C. at a heating rate of 2-5° C. / min in a nitrogen atmosphere, and keeping the temperature for 6-16 hours to obtain a reactant;
[0054] 5) The reactant obtained in step 4) is washed with acid and anhydrous ethanol for multiple times, filtered, and then ball-milled in a ball mill at 500-1000 r / min for 4-6 hours, and screened with a 180-400 mesh screen to obtain a carbon fiber material.
[0055] In a third aspect, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the carbon fiber material described in the first aspect.
[0056] In one embodiment, the negative electrode active material and the conductive agent in the negative electrode of the lithium ion battery are at least partially made of the carbon fiber material described in the first aspect, wherein the mass proportion of the carbon fiber material is 20-40%, such as 20%, 22.5%, 25%, 28%, 30%, 33%, 35%, 36%, 38% or 40%, etc., based on the total weight of the negative electrode active material layer. The lithium ion battery is prepared using the formula of this technical solution without adding other conductive agents. The negative electrode active material other than the above-mentioned carbon fiber material is a common negative electrode material in the prior art, for example, one or more of graphite, silicon, silicon oxide, carbon-coated silicon oxide, etc. can be selected.
[0057] The carbon fiber material of the present invention has the advantage of high conductivity. When it is used as both a negative electrode active material and a conductive agent in a lithium-ion battery, the step of adding a conductive agent can be omitted and the rate performance of the lithium battery can be improved.
[0058] In another embodiment, the negative electrode conductive agent in the negative electrode of the lithium-ion battery adopts the carbon fiber material described in any one of claims 1-7, wherein the mass proportion of the carbon fiber material is 2%-5% based on the total weight of the negative electrode active material layer, for example, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc.
[0059] The carbon fiber material of the present invention has high conductivity and is suitable for use as a conductive agent in the preparation of negative electrodes. It can fully or partially replace traditional conductive carbon materials such as Ketjen black, acetylene black, SP, etc., and improve the electrochemical performance of the battery.
[0060] By way of example and not limitation, the present invention provides an application of the above-mentioned carbon fiber material in the negative electrode of a lithium ion battery:
[0061] A negative electrode plate for a lithium-ion battery is prepared by using the above-mentioned carbon fiber material as a negative electrode conductive agent and an active material. The mass ratio of the components in the negative electrode plate for the lithium-ion battery: the carbon fiber material and the adhesive polyvinylidene fluoride (PVDF) and graphite is (20-40): (5-20): (40-65), wherein the selection range of the active material carbon fiber material is 20-40, such as 20, 25, 30, 35 or 40, etc.; the selection range of PVDF is 5-20, such as 5, 8, 10, 12, 15, 18 or 20, etc.; the selection range of the conductive agent acetylene black is 40-65, such as 40, 45, 50, 55, 60 or 65, etc.
[0062] The present invention does not specifically limit the type of lithium-ion battery, which can be a liquid battery or a solid-state battery. For a liquid battery, it generally includes a positive electrode, a negative electrode, a separator and an electrolyte, and for a solid-state battery, it generally includes a positive electrode, a negative electrode and a solid electrolyte layer.
[0063] In some embodiments, the lithium-ion battery is a flexible battery. Since the carbon fiber material prepared by the present invention has a porous network structure, the negative electrode has both mechanical strength and high electrochemical performance, and there are a large number of nano-voids therein, so that the flexible battery has a thinner size and a higher capacity.
[0064] Compared with the prior art, the present invention has the following beneficial effects:
[0065] (1) The graphitized carbon fiber material of the present invention has a porous network structure, which is conducive to improving the specific surface area and lithium storage performance of the material, allowing lithium ions to shuttle quickly, thereby improving its conductivity and rate performance. The micropores on the surface of the graphitized carbon fiber are conducive to the storage of lithium adsorbed ions on the surface and edges of the carbon fiber, thereby increasing the capacity.
[0066] The carbon fiber material of the present invention is used as a negative electrode active material in a lithium ion battery and has the advantages of high capacity, good conductivity and excellent rate performance.
[0067] (2) The method of the present invention can reduce the graphitization temperature due to the addition of iron element in the low eutectic solvent, thereby being able to prepare carbon fiber with a high degree of graphitization. At the same time, choline chloride is used to produce a corrosion pore-forming effect during the high-temperature graphitization treatment, thereby improving the specific surface area and lithium storage performance of the carbon fiber.
[0068] In the method of the present invention, since the fiber biomass carbon is directly carbonized with the low eutectic solvent, the phenomenon of uneven mixing of reactants in the precursor during the usual carbonization process is avoided, thereby improving the carbonization efficiency and uniformity, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] Figure 1 and Figure 2 The SEM images of the carbon fiber material prepared in Example 1 of the present invention at different magnifications;
[0070] Figure 3 This is the XRD pattern of the carbon fiber material prepared in Example 1 of the present invention;
[0071] Figure 4 A comparison diagram of the compaction density of the negative electrode sheets of Application Example 1 of the present invention and Comparative Application Example 1 under different pressures;
[0072] Figure 5 It is a comparison chart of the conductivity of the negative electrode sheets of Application Example 1 of the present invention and Comparative Application Example 1 under different pressures. DETAILED DESCRIPTION
[0073] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0074] Example 1
[0075] 1) 13.96 g of choline chloride and 21.20 g of ferric chloride were weighed in a molar ratio of 3:5, and stirred at 70° C. for 2 h in a constant temperature magnetic stirrer to obtain a deep eutectic solvent;
[0076] 2) weighing 17.28 g of lignocellulose and 17.28 g of a deep eutectic solvent in a mass ratio of 1:1, stirring the mixture in a constant temperature magnetic stirrer at 80° C. for 6 h to obtain a mixture;
[0077] 3) The mixture obtained in step 2) was subjected to ultrasonic oscillation at room temperature for 30 minutes using an ultrasonic machine, and then allowed to stand for 2 hours to obtain a precursor;
[0078] 4) The precursor obtained in step 3) is first heated to 200° C. at a heating rate of 2° C. / min in an air atmosphere and kept at this temperature for 2 h; then heated to 1600° C. at a heating rate of 5° C. / min in a nitrogen atmosphere and kept at this temperature for 12 h to obtain a reactant;
[0079] 5) The reactant obtained in step 4) was washed with dilute sulfuric acid and anhydrous ethanol for multiple times and then filtered; then ball milled in a ball mill at 800 r / min for 6 hours, and screened with a 270-mesh screen to obtain a carbon fiber material.
[0080] Figure 1 and Figure 2 These are SEM images of the carbon fiber material prepared in Example 1 of the present invention at different magnifications.
[0081] Figure 3 This is the XRD diagram of the carbon fiber material prepared in Example 1 of the present invention. It can be seen from the figure that the 002 peak of the carbon fiber material in Example 1 is obvious and has high intensity, while the background signal is low, and the degree of graphitization is high.
[0082] Example 2
[0083] Different from Example 1, in step 4, the temperature is increased to 1400° C. at a heating rate of 3° C. / min under a nitrogen atmosphere and kept at that temperature for 12 h to obtain a reactant.
[0084] Compared with Example 1, this example does not perform the pre-oxidation step, and the heating rate and the insulation temperature are lowered.
[0085] Example 3
[0086] Different from Example 1, in step 4, the temperature is increased to 1800° C. at a heating rate of 5° C. / min under a nitrogen atmosphere and kept at that temperature for 8 h to obtain a reactant.
[0087] Compared with Example 1, this embodiment does not perform the pre-oxidation step, and the insulation temperature is increased while the insulation time is decreased.
[0088] Example 4
[0089] Compared with the example, the present example 1 does not perform a pre-oxidation step, and the heating rate, the insulation temperature and the time are the same.
[0090] Example 5
[0091] The difference from Example 1 is that in step 1, choline chloride and ferric chloride are weighed in a molar ratio of 1:9.
[0092] Example 6
[0093] The difference from Example 1 is that in step 1, choline chloride and ferric chloride are weighed in a molar ratio of 2:1.
[0094] Example 7
[0095] This embodiment provides a carbon fiber material and a preparation method thereof, the method comprising the following steps:
[0096] 1) Choline chloride and ferrous chloride were weighed in a molar ratio of 2:3, and stirred at 70° C. for 3 h in a constant temperature magnetic stirrer to obtain a deep eutectic solvent;
[0097] 2) weighing lignocellulose and a low eutectic solvent in a mass ratio of 3:4, stirring the mixture in a constant temperature magnetic stirrer at 50° C. for 5 h to obtain a mixture;
[0098] 3) The mixture obtained in step 2) was subjected to ultrasonic oscillation at room temperature for 40 minutes using an ultrasonic machine, and then allowed to stand for 1 hour to obtain a precursor;
[0099] 4) The precursor obtained in step 3) is first heated to 280° C. at a heating rate of 4° C. / min in an air atmosphere, and kept warm for 2 h; then heated to 1550° C. at a heating rate of 5° C. / min in a nitrogen atmosphere, and kept warm for 10 h to obtain a reactant;
[0100] 5) The reactant obtained in step 4) was washed with dilute sulfuric acid and anhydrous ethanol for multiple times and then filtered; then ball milled in a ball mill at 800 r / min for 5 h, and screened with a 300-mesh screen to obtain a carbon fiber material.
[0101] Comparative Example 1
[0102] Different from Example 1, 13.96 g of choline chloride and 150 g of urea were weighed in a molar ratio of 3:5, and stirred at 70° C. for 2 h in a constant temperature magnetic stirrer to obtain a low eutectic solvent.
[0103] Application examples 1-7 and comparative application example 1:
[0104] The carbon fiber materials obtained in Examples 1-7 and Comparative Example 1 are used as conductive agents and part of the negative electrode active materials, and the adhesive polyvinylidene fluoride (PVDF) and graphite are weighed in a mass ratio of 35:15:50, and then N-methylpyrrolidone (NMP) is added and stirred evenly to form a slurry, which is then coated on the surface of the copper foil and dried in a drying oven at 80°C for 12 hours to obtain a prefabricated electrode sheet. The prefabricated electrode sheet is cut into electrode sheets after rolling and dried in a drying oven at 120°C for 8 hours to obtain the negative electrode sheets of Application Examples 1-7 and Comparative Application Example 1.
[0105] The test method of compaction density is as follows: the electrode rolled under different pressures is cut into 1CM*1CM square blocks, and the weight and thickness of the active material are tested. The corresponding compaction density is obtained by the weight of active material / (thickness of active material*area).
[0106] Conductivity test method: Based on the principle of Kelvin four-wire method, the conductivity is tested with a four-probe powder conductivity tester. The powder resistance test system MCP-PD51 and Loresta-GX MCP-T700 low resistance tester are connected for testing.
[0107] The test results of the compaction density and conductivity of the negative electrode sheets of Application Example 1 and Comparative Application Example 1 under different pressures are shown in Figure 4 , Figure 5 It can be seen that the conductivity and compaction density of Application Example 1 are better than those of Comparative Application Example 1.
[0108] Application Example 8
[0109] The carbon fiber material obtained in Example 1 is used as a conductive agent, and the adhesive polyvinylidene fluoride (PVDF) and graphite are weighed in a mass ratio of 5:15:85. Then N-methylpyrrolidone (NMP) is added and stirred evenly to form a slurry, which is applied on the surface of the copper foil and dried in a drying oven at 80°C for 12 hours to obtain a prefabricated electrode sheet. The prefabricated electrode sheet is cut into electrode sheets after rolling and dried in a drying oven at 120°C for 8 hours to obtain the negative electrode sheet of Application Example 8.
[0110] Comparative Application Example 2
[0111] Different from Application Example 8, acetylene black is used as the conductive agent to obtain the negative electrode sheet of Comparative Application Example 2.
[0112] Performance Testing
[0113] The above-mentioned pole pieces were assembled into a lithium-ion half-cell, with lithium metal as the counter electrode, the electrolyte being a diethyl carbonate (DEC) + ethylene carbonate (EC) solution containing 1 mol / L lithium hexafluorophosphate (volume ratio DEC:EC=7:3), and the diaphragm being polypropylene Celgard2300. The assembly was completed in a glove box.
[0114] The assembled half-cell was left to stand at room temperature for 12 h before constant current charge and discharge test. The charge and discharge voltage was 0-3 V. The constant current charge test was performed at 25 °C with a current density of 100 mA / g (the charge and discharge currents were consistent). The electrical performance of the obtained battery was tested. The test results are shown in Table 1.
[0115] Table 1
[0116]
[0117] It can be seen from Table 1 that the capacity and first efficiency of Application Example 1 are greater than those of Application Examples 2, 3, and 4. This is because the air pre-oxidation process can introduce carbonyl groups that are beneficial to electrochemical energy storage and enhance the cross-linking degree of the material; at the same time, the reactants can be further dried and easily oxidized impurities can be removed during the pre-oxidation process.
[0118] Application Example 1 is better than Application Examples 5 and 6 because the ratio of lignocellulose to low eutectic solvent in the mixture is different, and the etching effect produced when the choline cation in the low eutectic solvent decomposes during sintering is different. In Application Example 5, the ratio of choline cation is small, resulting in a small number of micropores produced by sintering, which reduces the lithium storage performance; in Application Example 6, the ratio of choline cation is large, although the number of micropores is increased, the solubility of lignocellulose is increased, resulting in a higher degree of granulation of the final product, an increase in specific surface area, and an increase in lithium consumption during the formation process, thereby reducing the initial effect.
[0119] pass Figure 3 , Figure 4 , Figure 5 It can be seen that the degree of graphitization of Application Example 1 is much greater than that of Comparative Application Example 1, and the compaction density under high pressure is close to the true density of graphite 2.3g / cm 3 , and the electrical conductivity is also better than that of Comparative Example 1. This is because a low eutectic solvent of halogenated iron salt is used in Application Example 1, which can reduce the graphitization temperature. Therefore, the carbon fiber negative electrode material prepared in Application Example 1 has a high degree of graphitization and better electrical conductivity than that of Comparative Example 1, and the compression performance at the particle level is better than that of Comparative Example 1.
[0120] The rate performance of Application Example 8 is significantly better than that of Comparative Application Example 2 because the carbon fiber material has good electrical conductivity.
[0121] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A carbon fiber material, characterized in that: The carbon fiber material comprises graphitized carbon fibers, the graphitized carbon fibers are overlapped with each other to form a porous network structure, there are nanostructure gaps formed by interlacing carbon fibers between the graphitized carbon fibers, and the surface of the graphitized carbon fibers has micropores; In the XRD spectrum of the carbon fiber material, the ratio of the main peak intensity of the 002 crystal plane to the total intensity of the miscellaneous peaks is 2-5:1; The carbon fiber material is obtained by the following preparation method, which comprises the following steps: (1) heating and mixing a choline halide and an iron halide in a molar ratio of (1-3):(2-8) to form a low eutectic solvent; (2) mixing the fibrous biomass carbon with the low eutectic solvent to obtain a precursor; (3) subjecting the precursor to high-temperature graphitization treatment to obtain the carbon fiber material; The temperature of the high temperature graphitization treatment is 1550-1800°C.
2. The carbon fiber material according to claim 1, wherein the micropores are obtained by etching fibrous biomass carbon with flue gas of a low eutectic solvent, wherein the low eutectic solvent comprises halogenated choline and halogenated iron salt.
3. A method for preparing a carbon fiber material according to claim 1 or 2, characterized in that the method comprises the following steps: (1) heating and mixing a choline halide and an iron halide in a molar ratio of (1-3):(2-8) to form a low eutectic solvent; (2) mixing the fibrous biomass carbon with the low eutectic solvent to obtain a precursor; (3) subjecting the precursor to high-temperature graphitization treatment to obtain the carbon fiber material; The temperature of the high temperature graphitization treatment is 1550-1800°C.
4. The method according to claim 3, characterized in that The choline halide in step (1) comprises at least one of choline chloride, choline bromide or their derivatives.
5. The method according to claim 3, characterized in that: The halogenated iron salt in step (1) includes any one or more of ferric chloride, ferrous chloride, ferrous bromide or their derivatives.
6. The method according to claim 3, characterized in that The temperature of the heating and mixing in step (1) is 40-80° C. and the time is 2-8 hours.
7. The method according to claim 3, characterized in that The heating and mixing process in step (1) is accompanied by stirring.
8. The method according to claim 3, characterized in that The fiber biomass carbon in step (2) is non-food biomass.
9. The method according to claim 8, characterized in that The non-food biomass in step (2) is at least one of bamboo fiber, wood cellulose or their derivatives.
10. The method according to claim 3, characterized in that: In step (2), the mass ratio of the fibrous biomass carbon to the low eutectic solvent is (1-3):(2-8).
11. The method according to claim 3, characterized in that The mixing temperature in step (2) is 40-80°C and the mixing time is 2-8h.
12. The method according to claim 3, characterized in that The mixing process in step (2) is accompanied by stirring.
13. The method according to claim 3, characterized in that After the mixing in step (2), ultrasonic oscillation and standing are sequentially performed.
14. The method according to claim 13, characterized in that The ultrasonic oscillation was performed at room temperature.
15. The method according to claim 13, characterized in that The ultrasonic oscillation time is 20-60 minutes.
16. The method according to claim 13, characterized in that The standing time is 1-2h.
17. The method according to claim 3, characterized in that Before the high-temperature graphitization treatment in step (3), the precursor is pre-oxidized.
18. The method according to claim 17, characterized in that The temperature of the pre-oxidation treatment is 200-300° C., and the insulation time is 1-2 hours.
19. The method according to claim 17, characterized in that The heating rate of the pre-oxidation treatment is 2-5°C / min.
20. The method according to claim 17, characterized in that The atmosphere of the pre-oxidation treatment is an oxygen-containing atmosphere.
21. The method according to claim 20, characterized in that The atmosphere of the pre-oxidation treatment is air atmosphere.
22. The method according to claim 3, characterized in that The holding time of the high temperature graphitization treatment in step (3) is 6-16 hours.
23. The method according to claim 3, characterized in that The heating rate of the high temperature graphitization treatment in step (3) is 2-5°C / min.
24. The method according to claim 3, characterized in that The atmosphere of the high temperature graphitization treatment in step (3) is an inert atmosphere, and the gas in the inert atmosphere includes at least one of nitrogen, helium and argon.
25. The method according to claim 3, characterized in that Step (3) After the high temperature graphitization treatment, the steps of pickling, washing, separation, ball milling and screening are performed in sequence.
26. The method according to claim 25, characterized in that The solvent used for pickling in step (3) is a pickling solvent, and the pickling solvent is selected from one or more of hydrochloric acid, sulfuric acid and acetic acid.
27. The method according to claim 25, characterized in that The solvent used for the cleaning is anhydrous ethanol.
28. The method according to claim 25, characterized in that The ball mill has a rotation speed of 500-1000 r / min and a milling time of 4-6 h.
29. The method according to claim 25, characterized in that The mesh number of the sieving is 180-400 meshes, and the sieve under is taken after sieving.
30. A lithium ion battery, characterized in that: The lithium-ion battery comprises the carbon fiber material according to claim 1 or 2.
31. The lithium ion battery according to claim 30, characterized in that The negative electrode active material and the conductive agent in the negative electrode of the lithium ion battery are at least partially made of the carbon fiber material according to claim 1 or 2, wherein the mass proportion of the carbon fiber material is 20-40% based on the total weight of the negative electrode active material layer; or The negative electrode conductive agent in the negative electrode of the lithium ion battery is the carbon fiber material according to claim 1 or 2, wherein the mass proportion of the carbon fiber material is 2%-5% based on the total weight of the negative electrode active material layer.
32. The lithium ion battery according to claim 30 or 31, characterized in that: The lithium ion battery is a flexible battery.
Citation Information
Patent Citations
Technology for preparing high-performance low-cost graphitized carbon fiber with joule heat technology
CN111962287A
Graphitized carbon material and preparation method thereof
CN109368632A
Carbon-nitrogen-lithium multi-phase doped lithium ion battery negative electrode material, preparation method of material, lithium ion battery negative electrode plate and lithium ion battery
CN109888181A